Urban and Natural Regeneration, Calamity and Pollution in Cicero’s post reditum Orations - Benvenuti, Francesca (Ciceroniana On Line, 2023)
The article investigates the presence and role of environment and ecology in Cicero’s post reditum speeches. In this corpus, the description of the external world, as well as of the ways humans interact with it, is coherent and homogenous and is characterised by a clear dichotomy. On Cicero’s return from exile, the environment experiences a natural and urban rebirth, bearing witness to the beneficial effects Cicero has on the external world in contrast to the environmental and urban destruction wrought by Clodius and his supporters. With a focus on the speeches’ literary, stylistic, and rhetorical aspects, the analysis shows how Cicero deploys descriptions of the natural and urban world to legitimise his political agenda and to delegitimise that of his enemies. Particular attention is devoted to the metaphorical use of environment-related terms, as adopted especially within the invective.